(untitled) (Malay Literature, 2012)
Ecocriticism is concerned with the relationship between literature and environment or how the relationships between humans and their physical world are reflected in literature. In this paper, we attempt to analyse selected poems of Muhammad Haji Salleh using some concepts from ecocriticism as an analytical lens. The premise of this paper is based on the poet’s symbiotic relationship which has become a significant feature of his work. Using six of his nature poems to exhibit Muhammad’s idea of mutual relationship between the human world and the natural world of environment, we show the poet’s concern about the slightest interference of human beings into the world of nature which results in the disruption of human-nature relationship. Muhammad Haji Salleh does not limit himself to presenting the brighter and darker side of nature, rather he has gone a step further to reveal the very concept of ecosystem and reflect the blossoming of ecological consciousness in modern Malaysian society. This approach of reading Muhammad Haji Salleh exhibits the current interest in the environment and the ways in which it has to be treated with respect and love. By explicating the intrinsic features of nature in his selected poems, we can inculcate environmental awareness and inspire ecological consciousness among people in Malaysia and elsewhere in the world. Keywords: Ecocriticism, ecosystem, interrelationship, ecological consciousness, poetry and Muhammad Haji Salleh